Comparative study of microbiological qualities between tap water of old Dhaka and new Dhaka with emphasis on the presence of fecal coliform bacteria - Juthi, Muniara (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirement for the degree of B.Sc in Microbiology, 2016.